Optimalisasi Peran Mahasiswa PPI (Persatuan Pelajar Indonesia) Stambuk 2020 sebagai Mitra Strategis Pengawas Pemilu 2024 - Ritonga, Fadli Amri; Warnisyah, Elly; Syahrin, Abu (Medan Resource Center, 2023)
This study aims to assess and optimize the role of PPI (Indonesian Student Association) Class of 2020 students as strategic partners in overseeing the 2024 elections. Students are considered to have significant potential as social watchdogs capable of safeguarding the integrity of the democratic process. Using a qualitative approach and descriptive methods, this research identifies the roles, challenges, and opportunities for students in monitoring election implementation, particularly in preventing violations during the campaign period. The findings show that active student involvement not only strengthens election oversight but also increases political awareness among the younger generation, making them critical and integrity-driven agents of change in upholding democracy.